Investigation of PM10 and PM2.5 in Ambient Air: Spatial and Temporal Variations in the Western Area of a Cement Plant - Apriandi. AD; Vera Surtia Bachtiar; Shinta Silvia (Universitas Negeri Padang, 2025)
The objective of this study is to evaluate the horizontal distribution of particulate matter concentrations (PM10 and PM2.5) in ambient air within the vicinity of the cement factory, with consideration for variations in spatial and temporal. The measurements were conducted using the EPAM 5000 instrument, with a total of six sampling points at distances of 0 km, 0.5 km, 1 km, 1.5 km, 2 km and 2.5 km, both during the day and at night, over a period of three days. Meteorological parameters such as air temperature, relative humidity, air pressure, and wind speed were measured to analyses their influence on particulate matter distribution. The findings revealed that the highest PM10 and PM2,5 concentrations were measured at the location closest to the factory (B1) with values of 113.98 μg/m³ and 75.73 μg/m³ at night and 52.80 μg/m³ and 28.27 μg/m³ during the day. A clear pattern of decreasing concentrations of both types of particulates as the distance from the source increases is evident, with a significant decrease occurring at a distance of 0-0.5 km. The PM2.5/PM10 ratio at night (0.67) was higher than during the day (0.56), indicating a greater contribution of fine particulates at night. Meteorological conditions play an important role in the distribution of particulate matter, in particular changes in wind direction and wind speed at night contribute to differences in the concentration and distribution of particulate matter. The results of this study indicate an increased risk of exposure to particulate matter in areas near factories, especially at night, which can be a basis for consideration in the preparation of air pollution control policies and efforts to safeguard public health.